“Crisis” or “opportunity”? COVID-19 pandemic's impact on environmentally sound invention efficiency in China - Wei, Xuan; Liu, Ranran; Lin, Zhouzhou (Frontiers in Public Health, 2023)
The environmentally sound invention (ESI) is a “bridge” between environmental sound technologies (ESTs) and green productions. This study investigates the COVID-19 pandemic’s impact on ESI efficiency using a multi-methods model in three stages. The ESI efficiency is measured using the Slack-Based Measure (SBM) method in the first stage. By excluding the environmental effect of the pandemic on each province using the stochastic frontier analysis (SFA) model’s results in the second stage, this study compares the ESI efficiency change with or without the influence of the pandemic in the third stage. The results show that the pandemic can be a “crisis” in the short term, but an “opportunity” in the long term. First, the SBM efficiency results in the first stage show a decrease in the number of the average efficient provinces in which the pandemic is more severe during 2020-2021. Second, results of the spatial Tobit and SFA models provide evidence that the COVID-19 pandemic negatively impacts the ESI efficiency during 2020, this impact is decreasing in 2021, and this impact has a spatial diffusion effect. Based on these results, this study discussed the theoretical and political implications. This paper enriches the knowledge of ESTs research and development by proposing a three-stage approach with multi-methods to investigate the influence of the pandemic’s impact on ESI efficiency.